2020
DOI: 10.1183/13993003.00130-2020
|View full text |Cite|
|
Sign up to set email alerts
|

Prospective validation of the RAPID clinical risk prediction score in adult patients with pleural infection: the PILOT study

Abstract: BackgroundOver 30% of adult patients with pleural infection either die and/or require surgery. There is no robust means of predicting at baseline presentation which patients will suffer a poor clinical outcome. A validated risk prediction score would allow early identification of high-risk patients, potentially directing more aggressive treatment thereafter.ObjectivesTo prospectively assess a previously described risk score (RAPID - Renal (urea), Age, fluid Purulence, Infection source, Dietary (albumin)) in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 47 publications
3
87
0
3
Order By: Relevance
“…Categorisation of patients in to low risk (RAPID score 0-2), medium risk (RAPID score 3-4) and high risk (RAPID score 5-7) groups was associated with mortality at 3 months of 3%, 9% and 31%, respectively [108]. Since its publication, positive correlation of clinical outcomes with the RAPID score has been demonstrated [109] and prospective assessment has recently been completed in an international, multicentre study [110] due to publish later this year. This should add greater insight into its potential utility in the clinical setting.…”
Section: Risk Scoring and Altering The Treatment Pathwaymentioning
confidence: 99%
“…Categorisation of patients in to low risk (RAPID score 0-2), medium risk (RAPID score 3-4) and high risk (RAPID score 5-7) groups was associated with mortality at 3 months of 3%, 9% and 31%, respectively [108]. Since its publication, positive correlation of clinical outcomes with the RAPID score has been demonstrated [109] and prospective assessment has recently been completed in an international, multicentre study [110] due to publish later this year. This should add greater insight into its potential utility in the clinical setting.…”
Section: Risk Scoring and Altering The Treatment Pathwaymentioning
confidence: 99%
“…Second, some of the clinical outcomes such as fibrinolytic use and surgical referral may have been confounded by other factors not related to the pleural infection alone. The recently presented PILOT (Pleural Infection Longitudinal Outcome Study) trial has demonstrated that a significant proportion of patients with the most serious pleural infection do not go on to have surgery due to frailty and/or comorbidity (31). Additionally, the routine use of the fibrinolytic agents tPA (tissue plasminogen activator)/DNase was not adopted for several years into this study's recruitment.…”
Section: Original Articlementioning
confidence: 99%
“…Now this score has been validated prospectively in the Pleural Infection Longitudinal Outcome (PILOT) study. Across 546 patients, the PILOT study demonstrated that low-risk patients (RAPID score 0–2) had a 3-month mortality of 2.3%, medium-risk (RAPID score 3–4) 9.2% mortality and high-risk (RAPID score 5–7) 29.3% mortality [ 106 ]. It is hoped that through the use of the RAPID score, a more nuanced approach can be taken in risk-stratifying patients and thereby informing clinicians of the optimal approaches in management.…”
Section: Surgerymentioning
confidence: 99%